PERAN KEPEMIMPINAN KEPALA MADRASAH DALAM PENGENDALIAN MUTU (Studi Kasus di MTs. Az-Zainiyah 1 Paiton, Probolinggo) - Abdurrahman Abdurrahman; Azizah Firdausi (al-fikrah: Jurnal Manajemen Pendidikan, 2019)
this study to analysis about which kind is the leader of Islamic boarding school station in restrainting quality of instituted under of it. That used in restraint method is feld research of yard restrain. From the resulf of research, we can take the conclution that is the leader of Islamic boarding school as spear for developing an instituted. To increase the school quality, the leader of Islamic boarding school should own good cleverness, and capable in developing new idea in order the institude afford to compete in globalization era and able to arrange organization inside it. The implication of this study is restrainting quality education if the holder of reins capable in performing the duty maximality.